THE IMPACT OF KEY AUDIT MATTERS DISCLOSURE ON COMMUNICATIVE VALUE OF THE AUDITOR’S REPORT: A SYSTEMATIC LITERATURE REVIEW - Yoga, Budhi Setiya; Dinarjito, Agung (UI Scholars Hub, 2021)
This research aims to discuss whether the disclosure of key audit matters (KAM) increases the communicative value of the auditor’s report. It also examines factors that need to be considered related to KAM disclosure. It is carried out in connection with the issuance of the Exposure Draft of Indonesia Audit Standard (AS) 701 on ”Pengomunikasian Hal Audit Utama dalam Laporan Auditor Independen” which was adopted from the International Standard on Auditing 701. In Indonesia, no research was found yet related to this topic. By conducting a systematic literature review of the latest articles from 2012 to 2021, this study found that KAM disclosure increases the communicative value of the auditor’s report, which is useful for report users in their decision-making. This study also informed specific areas that were often disclosed as KAM and provided information related to the factors that can decrease the communicative value of KAM disclosure. The results support the plan of AS 701 implementation in Indonesia because it will increase the communicative value of the auditor’s report. This study will be of interest to auditors in preparing the implementation of AS 701, report users in understanding KAM disclosure, and regulators as initial information regarding KAM disclosure to support their duties when AS 701 has been effectively implemented in Indonesia.